Financial Risk Determinants in Islamic Rural Banks: Static and Dynamic Models - Heri Sudarsono; Mohammad Hendrie Anto; Andika Perdana (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2024)
This study aims to determine the effect of financial performance on the financial risk of the Islamic Rural Bank (IRB) in Indonesia. The data period used from 2012 to 2019 on 65 IRBs using static and dynamic panels. The static panel test uses the common, fixed, and random effects, while the static panel uses the SYS-GMM test. The test results of 8 models on the static panel show that the best model is to use the random effect. The dynamic panel test shows the results of the AB test, Sargan test, PLS test, and FE test; it can be seen that the equation model has a consistent estimator. The data processing results show that the activities of the IRB, profitability, and economic growth have a negative relationship to the financial risk of the IRB. Then, the efficiency level of the IRB and inflation did not affect its financial risk. Finally, the policy implications of IRB management should adopt a cautious approach to financial risk management by recognising the inherent dangers in funding and financing policies.